Hubungan Konflik Peran Ganda Dengan Stres Kerja Pada Perawat Wanita Di Rumah Sakit Bhayangkara TK.III Manado - Jacobus, Indah Lestari; Yahya, Irma M; Riu, Silvia Dewi Mayasari (Pusat riset dan Inovasi Nasional, 2024)
Abstract Nurse work stress is a condition of the subjective outcome of an individual's life that can be an interaction between an individual and the working environment that can threaten and stress the psychological, physiological, and behavioral behavior of a nurse. Working stress has a negative impact on workers' physical and mental health, decreased performance, lack of career development, and loss of employment. The aim of this study is to find out the relationship between the conflict of double roles and work stress in female nurses at Bhayangkara Hospital, Manado. Research uses analytical descriptive research methods using cross sectional research design. 43 Subjekts were sampled using purposive sampling. Data collection using questionnaires. Analysed with Chi Square statistical tests. Results of the study age of 26-35 years 31 Subjekts (72.1%), the length of work 1-5 years 34 Subjekt (79.1%), number of children 1 child 22 Subjekts (51.2%). The result of the chi square test is given a p value of 0.022, where < α 0.05. The conclusion in this study is that there is a relationship between conflict of double roles and work stress in women nurses at Bhayangkara Hospital, Manado. It is hoped that the hospital will pay attention to the mental health of nurses to improve the quality of services.